Susceptibility of Grapevine Sucker and Green Shoot Wounds to Trunk Disease Pathogens - Makatini, G.J.; Halleen, F.; Mutawila, C.; Moyo, P.; Mostert, L. (South African Journal of Enology and Viticulture, 2023)
Grapevine trunk disease fungi infect vines through openings, primarily pruning wounds. The main objective of this study was to understand the role of sucker wounds and wounds made by the removal of green shoots from the stems of potted grapevines as potential points of infection for grapevine trunk disease pathogens. Six wine and four table grape vineyards of different ages were sampled in different production areas in the Western Cape grape region of South Africa. Isolations were made from 161 sucker wounds, and fungal pathogens were identified using morphology and DNA sequence analysis of the internal transcribed spacers (ITS1 and ITS2) and the 5.8S ribosomal RNA gene, the translation elongation factor 1alpha or the partial β-tubulin gene. The results show that 62% of the sucker wounds were infected by trunk disease pathogens, including Diaporthe ampelina, Diplodia seriata, Phaeomoniella chlamydospora, Phaeoacremonium minimum, Eutypella microtheca, Cryptovalsa ampelina and Neofusicoccum australe. Diaporthe ampelina was the most common, followed by D. seriata and P. chlamydospora, in both the wine and table grape sucker wounds. Under glasshouse conditions, wounds made by the removal of young green shoots on one-year-old potted grapevine plants were inoculated with spore suspensions of D. ampelina, E. lata, N. parvum, P. minimum and P. chlamydospora. After four months, all the inoculated pathogens could be re-isolated. This study shows that grapevine sucker and green shoot wounds are susceptible to different grapevine trunk disease pathogens and may therefore play a role in the epidemiology of trunk diseases.